Chronicling the Journey of the Society for the Advancement in Biology Education Research (SABER) in its Effort to Become Antiracist: From Acknowledgement to Action - Segura-Totten, Miriam; Dewsbury, Bryan; Lo, Stanley M.; Bailey, Elizabeth Gibbons; Beaster-Jones, Laura; Bills, Robert J.; Brownell, Sara E.; Caporale, Natalia; Dunk, Ryan; Eddy, Sarah L.; García-Ojeda, Marcos E.; Gardner, Stephanie M.; et al. (Frontiers in Education, 2021)
The tragic murder of Mr. George Floyd brought to a head long-standing issues of racial justice and equity. This prompted institutions of higher education to engage in long-overdue conversations about the role of scientific institutions in perpetuating racism. Similar to many professional societies and organizations, the Society for the Advancement of Biology Education Research (SABER), an international professional organization for discipline-based biology education researchers, has struggled with a lack of representation of People of Color (POC) within its membership. The events surrounding Mr. Floyd’s death prompted the members of SABER to engage in conversations to promote self-reflection and discussion on how the society could become more inclusive. In this article, we chronicle the journey of SABER in its efforts to become more inclusive and antiracist, which resulted in 12 concrete actions to support POC, increase their representation, and amplify their voices within SABER. We describe these actions, which included a self-study to determine challenges and identify ways to address them, a year-long seminar series on issues of social justice and inclusion, a special interest group to provide networking opportunities for and to center POC voices, and an increase in the diversity of keynote speakers at SABER conferences. We also discuss remaining challenges and future steps to continue to build a more welcoming, inclusive, and equitable space for all biology education researchers, especially our POC members. Ultimately, we hope that the steps undertaken by SABER will enable other professional societies to embark on their reflection journeys to further broaden scientific communities.